2019
DOI: 10.1590/0103-8478cr20190446
|View full text |Cite
|
Sign up to set email alerts
|

Free-living diazotrophs drive castor bean nitrogen input in tropical semiarid soils

Abstract: There are few studies of microbial diversity in castor bean soils in tropical semiarid environmental. Castor bean products have been widely used around the world justifying the commercial importance of ricinoculture in Brazil’ northeastern semiarid. There is no fertilization or maintenance of litter on the soils from the present study, so we hypothesized that the free-living diazotrophs microorganisms drive the nitrogen (N) input into these soils. We evaluated the communities’ structure and diversity of diazot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Among the single crops, castor bean (T12), an oilseed species with good capacity for extracting nutrients in deep layers (Savy Filho et al, 1999) and producing biomass (Favarato et al, 2017), stood out among other species, including legumes. Studies demonstrate the importance of the diversity and activity of free-living diazotrophs in the entry of N into soils cultivated with castor bean, being important for maintaining nitrogen stocks in the soil and microbial biomass over time (Mendes et al, 2015;Fracetto et al, 2019). In addition, this species showed similar or higher N accumulation capacity than treatments with a greater number of species, including in the root system.…”
Section: Nitrogen Accumulationmentioning
confidence: 96%
“…Among the single crops, castor bean (T12), an oilseed species with good capacity for extracting nutrients in deep layers (Savy Filho et al, 1999) and producing biomass (Favarato et al, 2017), stood out among other species, including legumes. Studies demonstrate the importance of the diversity and activity of free-living diazotrophs in the entry of N into soils cultivated with castor bean, being important for maintaining nitrogen stocks in the soil and microbial biomass over time (Mendes et al, 2015;Fracetto et al, 2019). In addition, this species showed similar or higher N accumulation capacity than treatments with a greater number of species, including in the root system.…”
Section: Nitrogen Accumulationmentioning
confidence: 96%
“…, through root exudates specially at early growth stages (Lesu eur et al 2013) or the transfer of15 N via free-living soil microorganisms(Fustec et al 2010;Jalonen et al 2009). The enrichment observed for HGE, where the gas was directly supplied to annual ryegrass roots, indicates BNF either by free-living diazotrophs(Fracetto et al 2019) or by associative microorganisms already found in annual ryegrass(Castanheira et al 2014). Biological N 2 xation has been reported in other grass and cereal species(Boddey and Dobereiner, 1995) Dobereiner (1966).…”
mentioning
confidence: 95%